Septic induced Abortion - Mubashra Naz (Journal of University Medical & Dental College, 2020)
Unsafe abortion is one of the major health problems in developing countries and a serious concern for women in their reproductive years. Unsafe abortion mostly ending up in septic induced miscarriages, septicemia and septic shock is a leading cause of maternal mortality and morbidity. Maternal mortality which is an indicator of prevailing obstetric care facilities in a country has risen to many folds in Pakistan in last two decades with septic miscarriages contributing to about third of total number of cases